Capital Expenditure Allocation and Its Impact on Improving Public Service Quality in Medan City (2019–2022) - Nelva Ananda; Pradita Tasyarani Ginting; Renny Maisyarah (International Journal of Management, Economic and Accounting, 2026)
This study aims to evaluate the allocation of Capital Expenditure within the APBD structure and its impact on the quality of Public Services in Medan City during the 2019–2022 period. As a vital instrument in regional development, capital expenditure is directed at the procurement of fixed assets that support education, health, and infrastructure facilities for the community. The research method used is descriptive quantitative, analyzing Budget Realization Reports and regional development achievement data. The results show that the dynamics of budget allocation in Medan City faced significant challenges due to refocusing policies during the pandemic; however, the effectiveness of expenditure management remains a decisive factor in maintaining the quality of service to the public. This research is expected to serve as a reference for local governments in optimizing the proportion of capital expenditure to promote sustainable community welfare.